The Conclusion of the Guide of the Perplexed in View of the Conclusion of The Nicomachean Ethics - Malʾakh, Asaf (AJS review, 2021)
One of the well-known conundrums of the Guide of the Perplexed, found in its last chapter, pertains to Maimonides's contradictory presentation of the hierarchy of human virtues and perfections. This article draws attention to a parallel between the paradox posed by the closing paragraphs of the Guide and the contradiction found in the concluding paragraphs of Aristotle's Nicomachean Ethics, a parallel that has never been noted by students of Maimonides. The intention here is not to make a categorical statement about Maimonides's position on the core issues of the relationship between the intellect and the moral virtues. Rather, it is to shed new light on the unexpected structure of the last chapter, and thus also provide a significant addition to the important debate about Maimonides's position on these issues.